Mexico : Staff Report for the 2002 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2002)
This 2002 Article IV Consultation highlights that the economic slowdown in the United States triggered a sharp weakening in Mexican economic activity in 2001 from the rapid pace in the preceding year. There was also a marked deceleration in domestic demand growth, as disposable income was adversely affected by a contraction in employment and confidence sagged. Economic activity rebounded strongly in the second quarter of 2002, as exports were supported by stronger demand from the United States and final domestic demand grew sharply.